TRANSLATING LITERARY IRONY: ELEMENTS FOR A PRACTICAL FRAMEWORK PIERRE SKOROV - Skorov, Pierre (Vertimo studijos, 2017)
This paper looks at the versatile and elusive concept of irony in literature from a translator’s perspective. It offers elements for a basic definition and for a classification of literary irony. It aims to provide the literary translator with a practical framework that would make it an easier task to identify and understand the various types of irony present in literature.